Sorted gene genealogies and species- specific nonsynonymous substitutions point to putative postmating prezygotic isolation genes in Allonemobius crickets - Noh, S.; Marshall, Jeremy L. (My University, 2016)
In the Allonemobius socius complex of crickets reproductive isolation is primarily accomplished via postmating prezygotic barriers. We tested seven protein-coding genes expressed in the male ejaculate for patterns of evolution consistent with a putative role as postmating prezygotic isolation genes. Our recently diverged species generally lacked sequence variation. As a result, omega-based tests were only mildly successful. Some of our genes showed evidence of elevated omega values on the internal branches of gene trees. In a couple of genes, these internal branches coincided with both species branching events of the species tree, between A. fasciatus and the other two species, and between A. socius and A. sp. nov. Tex. In comparison, more successful approaches were those that took advantage of the varying degrees of lineage sorting and allele sharing among our young species. These approaches were particularly powerful within the contact zone. Among the genes we tested we found genes with genealogies that indicated relatively advanced degrees of lineage sorting across both allopatric and contact zone alleles. Within a contact zone between two members of the species complex, only a subset of genes maintained allelic segregation despite evidence of ongoing gene flow in other genes. The overlap in these analyses was arginine kinase (AK) and apolipoprotein A-1 binding protein (APBP). These genes represent two of the first examples of sperm maturation, capacitation, and motility proteins with fixed non-synonymous substitutions between species-specific alleles that may lead to postmating prezygotic isolation. Both genes express ejaculate proteins transferred to females during copulation and were previously identified through comparative proteomics. We discuss the potential function of these genes in the context of the specific postmating prezygotic isolation phenotype among, our species, namely conspecific sperm precedence and the superior ability of conspecific males to induce oviposition in females.
Citation: Noh, S., & Marshall, J. L. (2016). Sorted gene genealogies and species- specific nonsynonymous substitutions point to putative postmating prezygotic isolation genes in Allonemobius crickets. Peerj, 4, 29. doi:10.7717/peerj.1678
Keywords: Positive Selection; Ejaculate Proteins; Haplotype Networks; Lineage; Sorting; Postmating Prezygotic Isolation